2011
DOI: 10.1042/bj20100773
|View full text |Cite
|
Sign up to set email alerts
|

A functional family-wide screening of SP/KLF proteins identifies a subset of suppressors of KRAS-mediated cell growth

Abstract: SP/KLF transcription factors comprise an emerging group of proteins that may behave as tumor suppressors. Incidentally, many cancers displaying alterations in certain KLF proteins are also associated with a high incidence of KRAS mutations. Therefore, we here investigate whether SP/KLF proteins suppress KRAS-mediated cell growth, and more importantly, the potential mechanisms underlying these effects. Using a comprehensive, family-wide screening of the 24 SP/KLF members, we discover that SP5, SP8, KLF2, KLF3, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
77
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(82 citation statements)
references
References 28 publications
4
77
0
1
Order By: Relevance
“…Some KLF members are emerging as tumor-suppressor genes due to their roles in the inhibition of proliferation, migration, and induction of apoptosis (30,31). KLF2, as a member of KLF family, is diminished in many cancers and possesses tumor-suppressor features such as inhibition of cell proliferation mediated by KRAS (32)(33)(34). Moreover, there is evidence that showed that EZH2 could silence KLF2 expression and block the tumor-suppressor features of KLF2, which is partly mediated by p21 (21).…”
Section: Discussionmentioning
confidence: 99%
“…Some KLF members are emerging as tumor-suppressor genes due to their roles in the inhibition of proliferation, migration, and induction of apoptosis (30,31). KLF2, as a member of KLF family, is diminished in many cancers and possesses tumor-suppressor features such as inhibition of cell proliferation mediated by KRAS (32)(33)(34). Moreover, there is evidence that showed that EZH2 could silence KLF2 expression and block the tumor-suppressor features of KLF2, which is partly mediated by p21 (21).…”
Section: Discussionmentioning
confidence: 99%
“…KLF14 belongs to the SP/KLF (Specificity protein/Krüppel-like factor) family which constitutes a group of transcription factors that are present in organisms ranging from yeast to vertebrates [22,23]. KLF14 is also characterized by the presence of three highly conserved C-terminal Cys2His2 zinc finger domains responsible for DNA binding and regulates the transcription of various genes.…”
Section: Introductionmentioning
confidence: 99%
“…Представители семейства Sp-белков (называемые также krüppel-like factors -KLF) связы-ваются с так называемыми Sp1-сайтами (GC-бокс, GT-бокс, CACCC-бокс) промоторов или энхансеров различных генов и регулируют их экспрессию, уча-ствуя в клеточной пролиферации, ангиогенезе, апоп-тозе и опухолевой прогрессии. Их молекулы вклю-чают три высококонсервативных ДНК-связывающих домена (65 % сходства нуклеотидной последова-тельности у различных членов семейства), каждый из которых формирует структуру типа «цинковый палец» на С-конце и способствует связыванию транскрипционного фактора с соответствующими участками генома и межбелковым взаимодействи-ям, вариантный N-концевой домен, ответственный за трансактивационную или ингибирующую актив-ность и способность связываться с корепрессорами и коактиваторами, а также структуру, регулирую-щую ядерную локализацию фактора [10, 15,18,22]. В активации и ингибировании экспрессии генов под влиянием членов Sp1/KLF-семейства ведущая роль отводится деацетилированию и ацетилированию ги-стонов [18].…”
Section: Aadsorasunclassified